The Role of Youth to Improve Community Literacy about Covid-19 - Alim Harun Pamungkas (Universitas Negeri Padang, 2020)
Youth is one of the main targets of sustainable development. Target in the sense of being a development target and also as an executor of development. Some official data sourced from the UN and ADB show the disadvantaged situation of youth in several regions of the world. However, in other data, it is shown that the existence of youth is a new optimism in the world's sustainable development towards 2030. In the case of Covid-19 as a world pandemic, youth play a role in several concrete actions, either as volunteers or as agents of information dissemination that have an impact on related public literacy Covid-19 prevention. Mainly in the case in Indonesia.Keywords: Youth, Community Literacy, Covid-19